2022
DOI: 10.18632/aging.204058
|View full text |Cite
|
Sign up to set email alerts
|

Sperm DNA integrity is critically impacted by male age but does not influence outcomes of artificial insemination by husband in the Chinese infertile couples

Abstract: The sperm chromatin structure assay (SCSA) is crucial for assessing male fertility. However, the predictive value of the SCSA parameters, including the DNA fragment indices (DFI) and the percentages of high DNA stainability (HDS), for outcomes of artificial insemination by husband (AIH) remains controversial. This study aims to evaluate the correlations between SCSA parameters and male aging as well as other routine semen parameters, and explore their prognostic powers on AIH outcomes of the Chinese infertile … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 37 publications
1
6
0
Order By: Relevance
“…DFI increased with age; the older the age, the higher the DFI. These results are consistent with those of other studies, that indicated age is a critical factor for male fertility (14)(15)(16)(17).…”
Section: Relationship Between Age Pr% and Dfisupporting
confidence: 94%
“…DFI increased with age; the older the age, the higher the DFI. These results are consistent with those of other studies, that indicated age is a critical factor for male fertility (14)(15)(16)(17).…”
Section: Relationship Between Age Pr% and Dfisupporting
confidence: 94%
“…We found that APA had an impact on DNA fragmentation. In fact, a detrimental effect of age has already been reported on DNA fragmentation; chromatin decondensation and even on sperm aneuploidy rates [37]. The statement suggests that advanced male age can have a negative influence on fertility potential, similar to the impact on women.…”
Section: Discussionmentioning
confidence: 96%
“…Whether sperm DFI could represent semen parameters and provide clinical diagnosis of patient's semen quality, needed investigations [13][14][15]. Studies showed increased sperm DFI in infertile males with abnormal semen parameters [16].…”
Section: Discussionmentioning
confidence: 99%